2018
DOI: 10.1002/dvg.23215
|View full text |Cite
|
Sign up to set email alerts
|

Neural crest Notch/Rbpj signaling regulates olfactory gliogenesis and neuronal migration

Abstract: SummaryThe neural crest‐derived ensheathing glial cells of the olfactory nerve (OECs) are unique in spanning both the peripheral and central nervous systems: they ensheathe bundles of axons projecting from olfactory receptor neurons in the nasal epithelium to their targets in the olfactory bulb. OECs are clinically relevant as a promising autologous cell transplantation therapy for promoting central nervous system repair. They are also important for fertility, being required for the migration of embryonic gona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 86 publications
0
11
0
Order By: Relevance
“…Further, these observations suggest that the near complete absence of Sox10 ϩ OECs in the nasal mucosa of Gli3 Xt/Xt mutants is not a only the result of defective vomeronasal neurogenesis (Fig. 8O) (Miller et al, 2018;Rich et al, 2018), but likely secondary to neural crest defects (Matera et al, 2008). In support of this conjecture, we observed that Gli3 Xt/WT /Ascl-1 ϩ/Ϫ double mutants were indistinguishable from Gli3 Xt/WT single mutants (data not shown).…”
Section: Ascl-1 Loss-of-function Compromises Vno and Gnrh-1 Neurogenementioning
confidence: 53%
See 2 more Smart Citations
“…Further, these observations suggest that the near complete absence of Sox10 ϩ OECs in the nasal mucosa of Gli3 Xt/Xt mutants is not a only the result of defective vomeronasal neurogenesis (Fig. 8O) (Miller et al, 2018;Rich et al, 2018), but likely secondary to neural crest defects (Matera et al, 2008). In support of this conjecture, we observed that Gli3 Xt/WT /Ascl-1 ϩ/Ϫ double mutants were indistinguishable from Gli3 Xt/WT single mutants (data not shown).…”
Section: Ascl-1 Loss-of-function Compromises Vno and Gnrh-1 Neurogenementioning
confidence: 53%
“…Moreover, Gli3 Xt/WT /Ascl-1 ϩ/Ϫ double mutants did not have exacerbated phenotypes compared with Gli3 Xt/WT suggesting that the effects seen in both Ascl-1 null and Gli3 Xt/Xt are independent of each other and not additive (data not shown). We conclude that the near complete absence of OECs in the nasal mucosa of Gli3 Xt/Xt mutants is not secondary to the decreased number of vomeronasal fibers (Miller et al, 2018).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…During development, Notch receptors can regulate gross neuronal morphology and fine synaptic architecture through both canonical and non-canonical signaling in diverse species. This includes regulation of neuronal migration [ 144 , 145 , 146 , 147 ], neurite outgrowth and morphogenesis [ 148 , 149 , 150 , 151 , 152 , 153 , 154 , 155 , 156 , 157 , 158 ], axon guidance and targeting [ 159 , 160 , 161 , 162 , 163 , 164 ], dendrite morphogenesis [ 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 ], synaptogenesis [ 173 , 174 ], and synaptic growth [ 121 , 175 ]. Hence, one may consider that Notch signaling may regulate neuronal and synaptic physiology by fine-tuning cellular mechanisms that lead to structural alterations in the post-developmental brain.…”
Section: Mechanisms By Which Post-developmental Notch Signaling Rementioning
confidence: 99%
“…The initiating molecular events of SCLC are believed to be inactivation of TP53 and RB1, which mainly occurs in Kulchitsky cells in the respiratory epithelium, although many other genes and signaling pathways are disrupted, especially Notch signaling [114]. Notch signaling play various roles during neural crest development, especially in neurons differentiation [115,116]. Interestingly, TAMs are probably involved in SCLC progression through STAT3 activation and TAM-derived IL-6 can be one of molecules related to STAT3 activation in SCLC cells [117].…”
Section: Tumors Of Not Established Nc Originmentioning
confidence: 99%